Haemoglobin uptake in ring stage parasite-infected erythrocytes containing a fluorescent endocytic marker, tmr-dextran - Othman, Siti Fairuz (Universiti Sains Malaysia, 2015)
Early studies of the endocytic process in malaria parasite-infected erythrocytes showed that uptake of the host erythrocyte cytoplasm is most active in mature stage parasites (trophozoites). The parasite was thought to feed by distinct endocytic structures termed cytostomes. Vesicles that bud from the cytostomes were proposed to migrate to and fuse with the digestive vacuole where haemoglobin digestion and haem detoxification were thought to take place. Recent studies using serial thinsection electron microscopy however have led to conflicting conclusions. Hence, the aim of this work was to re-examine the endocytic process of live and intact parasites under non-disruptive conditions using live cell imaging by confocal microscopy. Resealed erythrocytes containing an endocytic marker, TMR-dextran were prepared using an optimised ratio of erythrocyte to haemolysis buffer volume (1:3) to minimise loss of haemoglobin while achieving a relatively homogenous population. TMR-dextran labelled erythrocytes were invaded by the parasites with similar efficiency to normal erythrocytes. Young stage parasites (rings) based on the estimated time after invasion and the absence of haemozoin showed punctate structures containing TMR-dextran near the parasite periphery suggesting that they probably represent early endocytic events.